The effect of seasonally frozen ground on rainfall infiltration and groundwater discharge in Qinghai Lake Basin, China - Ding, Chen; Guo, Zhilin; Chen, Kewei; Fan, Linfeng; Zhan, Yang; Kuang, Xingxing; Cui, Buli; Zheng, Chunmiao (Frontiers in Water, 2024)
Seasonally frozen ground (SFG) is a significant component of the cryosphere, and its extent is gradually increasing due to climate change. The hydrological influence of SFG is complex and varies under different climatic and physiographic conditions. The summer rainfall dominant climate pattern in Qinghai Lake Basin (QLB) leads to a significantly different seasonal freeze–thaw process and groundwater flow compared to regions with winter snowfall dominated precipitation. The seasonal hydrological processes in QLB are not fully understood due to the lack of soil temperature and groundwater observation data. A coupled surface and subsurface thermal hydrology model was applied to simulate the freeze–thaw process of SFG and groundwater flow in the QLB. The results indicate that SFG begins to freeze in early November, reaches a maximum freezing depth of approximately 2 meters in late March, and thaws completely by June. This freeze–thaw process is primarily governed by the daily air temperature variations. During the early rainy season from April to June, the remaining SFG in deep soil hinders the majority of rainwater infiltration, resulting in a two-month delay in the peak of groundwater discharge compared to scenario with no SFG present. Colder conditions intensify this effect, delaying peak discharge by 3 months, whereas warmer conditions reduce the lag to 1 month. The ice saturation distribution along the hillslope is affected by topography, with a 10 cm deeper ice saturation distribution and 3 days delay of groundwater discharge in the steep case compared to the flat case. These findings highlight the importance of the freeze–thaw process of SFG on hydrological processes in regions dominated by summer rainfall, providing valuable insights into the hydro-ecological response. Enhanced understanding of these dynamics may improve water resource management strategies and support future research into climate-hydrology interactions in SFG-dominated landscapes.